Sharer Repurchases : The Malaysian Perspective - Chan, Kit Meng (2005)
There are various hypotheses for explaining why firms repurchase shares. In the Malaysian environment, the leverage hypothesis best explains the share repurchasing behavior of firms. The pre-dominance of the leverage hypothesis is due to share repurchases being financed with additional debt or excess cash, both of which increase the debt/equity ratio. In relation to payout policy, analysis of payout trends reveal that repurchasing firms generally do not cut their dividends, and replace them with repurchases. They increase dividends in tandem with increase in earnings, and repurchase shares to augment payout ratios. Repurchasing firms generally have higher dividend payout ratios than nonrepurchasing firms. Share repurchases have not replaced special dividends, and they increase firm’s financial flexibility. In comparing the financial characteristics of repurchasing firms with nonrepurchasing firms, repurchasing firms are observed to have slightly lower market to book ratios, lower levels of liquidity, and higher leverage ratios. Additionally,repurchasing firms pay higher dividends, and are marginally more profitable than nonrepurchasing firms.